Application of AHP and Profile Matching Methods in Teacher Performance Assessment at XYZ School - Hidayat, Wahyu; Puspasari, Ratih (Jurnal ICT : Information and Communication Technologies, 2025)
Teacher performance evaluation plays a critical role in improving educational quality; however, manual assessment systems often lead to subjectivity, inefficiency, and a lack of data-driven decision-making. This study aims to develop and implement a decision support system for teacher performance evaluation using the Analytical Hierarchy Process (AHP) and Profile Matching (PM) methods to produce more objective, transparent, and systematic assessments. The research was conducted at XYZ School with a sample of 20 teachers, evaluating five key performance aspects: learning planning, learning implementation, assessment and evaluation, classroom management, and communication with students. The AHP method was applied to determine the weight of each criterion through pairwise comparisons, while the Profile Matching method was used to align individual teacher competencies with ideal performance profiles. The system generated a ranking of teachers, identifying Drs. Hendarto Wijaya, Masriyanti, S.Pd, and Nurlia Syafina, S.Pd as the top three performers. The results indicate that combining AHP and PM effectively reduces subjectivity, enhances assessment accuracy, and accelerates the evaluation process. Furthermore, the web-based implementation allows automated reporting and easier data access, improving efficiency in teacher development planning. The implications of this study highlight that integrating multi-criteria decision-making models in educational management can strengthen evidence-based performance evaluation practices. Future studies should expand this framework across multiple institutions and incorporate advanced analytical methods to enhance system adaptability and scalability.